Effect of Elevated Temperature and CO2 Concentration on Disease Incidence, Severity and Yield of Wheat, Cabbage and Tomato - Md. Tanbir Rubayet; Preangka Saha Briste; Md. Abdullah Al Mamun; Farhana Prodhan; Md. Abdul Kader; Rayhanur Jannat; Md. Motaher Hossain; Md. Mizanur Rahman; Jatish Chandra Biswas (Future Science, 2026)
This study investigated the effects of elevated temperature and carbon dioxide (CO₂) on disease incidence, severity, and yield impacts in wheat (Triticum aestivum), cabbage (Brassica oleracea), and tomato (Solanum lycopersicum) under open-field and nethouse conditions. The pathogens evaluated included Rhizoctonia solani, Sclerotium rolfsii, Bipolaris sorokiniana, Alternaria brassicae, and Fusarium oxysporum f. sp. lycopersici. During the experimental period, maximum and minimum temperatures reached 39.3 °C and 11 °C in nethouse conditions compared with 37.5 °C and 9 °C in the open field, while CO₂ concentration was 388–395 ppm in the nethouse and 385 ppm in ambient air. Elevated CO₂ and temperature consistently increased disease incidence and severity. In wheat, sclerotium wilt showed the highest incidence (55.6%); in cabbage, both sclerotium wilt and Alternaria blight reached 100%; and in tomato, sclerotium wilt also caused 100% incidence. These infections were associated with significant yield reductions across all crops. To our knowledge, this is the first report from Bangladesh quantifying crop disease yield interactions under elevated temperature and CO₂, underscoring the vulnerability of key crops to climate change and the urgent need for adaptive management strategies.